Amazing new Amphipoda (Crustacea, Epimeriidae) from New Zealand’s deep-sea - Lörz, Anne-Nina; Coleman, Charles Oliver (Zootaxa, 2014)
Epimeriidae is an amphipod family with a worldwide distribution. Two new species have been discovered off New Zealand; Epimeria sophie sp. nov. and Epimeria emma sp. nov. Two new species have been discovered off New Zealand; Epimeria sophie sp. nov. and Epimeria emma sp. nov., which are described here in detail. This increases the number of Epimeria species known from New Zealand’s deep-sea to seven. The morphological differences of the juveniles with the adult of Epimeria sophie sp. nov. are discussed. Extensive scanning electron microscope images reveal structurally very complex surface arrangements on Epimeria emma sp. nov. A key to the 14 species of Pacific Epimeria is provided.